Convergence of Cultural and Historical Heritage Financing Models as a Factor in the Development of Knowledge-Based Economy in Russia - GORYAINOVA, Liudmila Vladimirovna; KRISHTAL, Igor Semenovich; KUZNETSOVA, Olga Dmitrievna; LISOVSKAYA, Ekaterina Gennadievna (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018DO - 10.14505//jemt.9.4(28).14, 2018)
The article substantiates the importance of the synthesis of new spiritual values and traditional cultural and historical objects for increasing human capital asset in knowledge-based economy conditions, which necessitates an increase in their funding. The role of the cultural capital as a theoretical basis of heritage research is revealed. It is demonstrated that the concept of the cultural capital, linking the economic and cultural spheres, leads to an understanding of the regularity of expectations of return on investment in cultural heritage objects and thus develops integration processes: objects are involved in economic activity, becoming attractive to investors. The hypothesis of convergence of cultural and historical heritage objects financing models was put forward and confirmed, the results of which are: the formation of a new financing model and heritage ecosystem, including actors in the process, technology, funding and institutional environment. The features of a new model of cultural heritage financing are revealed: the use by the state, along with budgetary allocations, of indirect support measures through tax preferences and social technologies, as well as the attraction of private investment through public-private partnerships, charity, grants, endowment funds.